Modern perspectives in sequential therapy for metastatic colorectal cancer with reference to the use of regorafenib - M. I. Sekacheva (IP Habib O.N., 2020)
Over the past two decades, many new variants of targeted therapy for metastatic colorectal cancer (mCRC) had appeared, and significantly increased patient survival. However, there were questions relating to the definition of the optimal sequence and the combination of different drugs. Cytotoxic agents, including irinotecan, oxaliplatin, 5-fluorouracil and capecitabine, are the basis of the treatment of mCRC. In addition, the arsenal of modern oncologist includes the group of drugs inhibiting the epidermal growth factors (for example, cetuximab and panitumumab) and inhibiting tumor angiogenesis factors (for example, bevacizumab and aflibercept). Moreover, the use of immuno-oncology drugs, trastuzumab or encorafenib is possible in case of knowing tumor-specific molecular signature. Unfortunately, these new indications can be used only in small proportion of patients. The multikinase inhibitor regorafenib takes a special place, it can be used in patients in spite of RAS mutation status. The increasing attention has been paid to the selection of the drugs for sequential therapy of mCRC, recently. This review discusses important clinical data on the direct role of targeted drugs in the treatment of mCRC in different subgroups of patients.